Recombinant DNA technology and genetic engineering - Rajagopal, K. (Tata McGraw-Hill Education, 2012)
Designed to fulfill the needs of undergraduate and postgraduate life science students, the book provides comprehensive knowledge of the fundamental principles and concepts in the subject. The unique feature of the book is the extensive use of illustrations for explaining the concepts and experiments. Further concepts have been aided with 'hands on techniques' for select procedures